Pengembangan Mobile Seamless Learning Platform untuk Meningkatkan Pengetahuan Kader PKK - Juwita, Mia Ratna; Ulfa, Saida; Wedi, Agus (JKTP: Jurnal Kajian Teknologi Pendidikan, 2023)
The number of Empowerment and Family Welfare Cadres which are called PKK Cadres, is very large and spread all over Indonesia, making the state budget unable to reach all of them to obtain increased capacity of Human Resources (HR), for this reason a mobile seamless learning platform is being developed to increase the knowledge of PKK Cadres. This research and development aim to produce a platform to increase the knowledge of PKK Cadres and test the level of product feasibility, using the Lee & Owens model. In addition, to determine whether there is an increase in the knowledge of PKK Cadres, a paired/dependent sample t-test was performed on the pretest and posttest value data. The product developed is a mobile seamless learning platform and is equipped with content in the form of reading materials, PowerPoint presentation materials, videos and learning evaluation tests. The platform validation results produce very good criteria based on material aspects as well as media and learning design aspects. The response of PKK cadres and teachers obtained very good criteria for the feasibility of the platform as a learning medium. Based on the results of statistical tests, it was concluded that there was an increase in the knowledge of PKK Cadres after using the mobile seamless learning platform.AbstrakJumlah Kader PKK yang sangat besar dan tersebar di seluruh penjuru Indonesia, membuat anggaran negara belum mampu menjangkau seluruhnya untuk memperoleh peningkatan kapasitas Sumber Daya Manusia (SDM), untuk itu maka dilakukan pengembangan mobile seamless learning platform untuk peningkatan pengetahuan Kader PKK. Penelitian dan pengembangan ini bertujuan untuk menghasilkan platform untuk meningkatkan pengetahuan Kader PKK dan menguji tingkat kelayakan produk, dengan menggunakan model multimedia based instructional design Lee & Owens. Produk yang dikembangkan berupa aplikasi mobile seamless learning platform dan dilengkapi dengan konten berupa bahan bacaan, bahan tayang powerpoint, video dan tes evaluasi pembelajaran. Hasil validasi platform menghasilkan skor rata – rata sebesar 88,05% dengan kriteria sangat baik, aspek materi 94,67% serta aspek media dan desain pembelajaran 84,33 %. Respon Kader PKK mendapat skor 89,74% dan respon pengajar mendapatkan skor 92,31% kesimpulannya platform memiliki kriteria yang sangat baik untuk kelayakan platform sebagai media pembelajaran. Selain itu untuk mengetahui adanya peningkatan pengetahuan Kader PKK dilakukan uji statistik paired/dependent sample t-test sehingga diperoleh kesimpulan terdapat peningkatan pengetahuan Kader PKK setelah menggunakan mobile seamless learning platform.